2011
DOI: 10.1007/s10286-011-0150-6
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of autonomic dysfunction in the fibromyalgia patients

Abstract: The cardiac autonomic function is normal and the autonomic reflex arc seems to be intact in the patients with fibromyalgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(85 citation statements)
references
References 19 publications
(19 reference statements)
12
73
0
Order By: Relevance
“…* Correlation is significant at the 0.05 level. the frequency-domain [3,4,8,32]. In the review by Meeus et al [33], a similar result was observed but in a meta-analysis from 2009 by Tak et al [34] this difference did not reach significance for a subgroup of FM patients although the difference was significant for a compound group with functional somatic disorders.…”
Section: Hrvmentioning
confidence: 47%
See 3 more Smart Citations
“…* Correlation is significant at the 0.05 level. the frequency-domain [3,4,8,32]. In the review by Meeus et al [33], a similar result was observed but in a meta-analysis from 2009 by Tak et al [34] this difference did not reach significance for a subgroup of FM patients although the difference was significant for a compound group with functional somatic disorders.…”
Section: Hrvmentioning
confidence: 47%
“…HRV is measured for several different parameters and in individuals presenting FM. These parameters are deviant and lower in comparison with the HRV observed in healthy reference persons [3,6,7]. Parasympathetic hypoactivity in women with FM may be detected through HRV measurements and has been associated with poor sleep quality [5,8] and chronic fatigue syndrome [9].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Most of the studies combined both time and frequency domain analysis [10,[24][25][26][27][28][29][30][31][32].…”
Section: Outcome Measuresmentioning
confidence: 99%